Educational Technology Research: Contexts, Complexity and Challenges. Issue 1 (26th February 2021) - Scanlon, Eileen
This paper explores the development of educational technology research over the last 50 years. This is done by considering what has influenced this development and what are current trends. The issue is further explored by considering what influence these trends have had on the development of distance learning pedagogy, especially for the education of adults. Technology Enhanced Learning or educational technology research (TEL) is a relatively young area of research. The work of educational technologists and others involved in education research has indeed been interdisciplinary. So, part of the exploration of trends in this paper has been directed towards understanding the impact of other areas of research on progress in educational technology research. A central focus of the paper is the understanding of how the "TEL Complex" (Scanlon et al. 2013 ) encapsulates some of these influences both from interdisciplinary perspectives and from an understanding of the complexity which has to be considered as part of the situatedness of the developments. The paper discusses some key contemporary trends in educational technology research. These are identified as personalisation, social learning, learning design, machine learning, and data driven improvement. These are worthy of exploration, in part, because each has a basis in early work in the field and therefore illustrate some continuing concerns. The paper concludes by acknowledging the broader influences on the development of educational technology and the complexity of the challenges facing the field and its practical applications.